Safety distance awareness system for Malaysian Driver - Pandak Jabo, Nurul Izzati (2013)
It is known that the risk of an accident increases exponentially with the speed of the vehicle and most collisions happen when the driver fails to brake at the required time and distance. The objective of this research is to create a Safety Distance Awareness System which aims at warning the driver of the potential frontal collision and to alter Malaysian driver attitudes. This system is to manipulate Malaysian driver attitude that likes to tailgating and to prevent rear-end collision in Malaysia. This is done by using a Sound Navigation and Ranging (SONAR) range finder to determine the distance of the vehicle or obstacle in front of the host vehicle. With the help of microcontroller, the distance of the host vehicle could be determined and a warning will be issued in the form of both visual and hearing so driver could take the correct preventive measure. There will be few stages of warning, the system will intensify the distress warning until the collision occurs. These SDAs do not take any automatic prevention or control to the vehicle to avoid collision. In overall the research hopes to achieve a more convenient driving experience and a safer driving environment by implementing the SDAS to keep drivers aware of the potential hazards ahead of their vehicle. Hopefully the Malaysian government will involve in this research, since the implementation of Safety Distance Awareness System can provide a new alternative in the safety system hence it can reduce accidents in Malaysia.